2013
DOI: 10.1080/13607863.2013.856865
|View full text |Cite
|
Sign up to set email alerts
|

Are self-efficacy beliefs and subjective task demand related to apathy in aging?

Abstract: These results shed new light on the processes related to apathy in aging and open up an interesting prospect for psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
2
14
0
1
Order By: Relevance
“…Supporting previous research, the influential role of depression in the model indicates the importance of early diagnosis and adequate treatment of depressive symptoms among older adults (Casey, 2012;Moussavi et al, 2007). Similarly, the role of self-efficacy in the model highlights the importance of enhancing perceptions of competence among older adults (Clark & Dodge, 1999;Grembowski et al, 1993), particularly given that self-efficacy beliefs are more likely to diminish with age (Esposito, Gendolla, & Van der Linden, 2014). The identification of physical activity as a lifestyle behaviour that is associated with psychological well-being and quality of life is consistent with a large body of work demonstrating the benefits of physical activity across numerous domains (Bauman, Merom, Bull, Buchner, & Fiatarone Singh, 2016;Daskalopoulou et al, 2017).…”
Section: Discussionsupporting
confidence: 65%
“…Supporting previous research, the influential role of depression in the model indicates the importance of early diagnosis and adequate treatment of depressive symptoms among older adults (Casey, 2012;Moussavi et al, 2007). Similarly, the role of self-efficacy in the model highlights the importance of enhancing perceptions of competence among older adults (Clark & Dodge, 1999;Grembowski et al, 1993), particularly given that self-efficacy beliefs are more likely to diminish with age (Esposito, Gendolla, & Van der Linden, 2014). The identification of physical activity as a lifestyle behaviour that is associated with psychological well-being and quality of life is consistent with a large body of work demonstrating the benefits of physical activity across numerous domains (Bauman, Merom, Bull, Buchner, & Fiatarone Singh, 2016;Daskalopoulou et al, 2017).…”
Section: Discussionsupporting
confidence: 65%
“…Indeed, theoretical models of self-efficacy postulate that the latter determines in part how much effort an individual will invest to achieve a goal (Bandura 1995). In this perspective, Esposito et al (2013) have recently showed in elderly people that the subjective demand of a memory task (i.e., perceived difficulty and estimated effort) operated as a mediator between self-efficacy beliefs and apathy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown the implication of different psychological mechanisms in the various facets of apathy. Thus, in elderly subjects, lack of initiative has been associated with difficulties in the ability to run multiple tasks simultaneously (''multitasking'') [18], difficulties in prospective memory [14] and also low self-efficacy beliefs [19]. To be more precise, Esposito et al [18] showed that the number of rules breaks on the modified Six Elements Test [20] was a significant predictor of lack of initiative in persons with a diagnosis of Alzheimer's disease.…”
Section: Manifestations Of Apathymentioning
confidence: 98%